Labor induction with misoprostol vaginal insert compared with dinoprostone vaginal insert. (18th June 2019) - Maggi, Claudia; Mazzoni, Giorgia; Gerosa, Vera; Fratelli, Nicola; Prefumo, Federico; Sartori, Enrico; Lojacono, Andrea
Abstract: Introduction: Misoprostol vaginal insert could lead to a significant reduction in the time to vaginal delivery, and an increase in the proportion of women achieving vaginal delivery, compared with dinoprostone vaginal insert. We compared the delivery outcomes of misoprostol 200 μg vaginal insert and dinoprostone 10 mg vaginal insert for induction of labor in women with an unfavorable cervix. Material and methods: This is a retrospective observational study conducted on a cohort of 220 women with a Bishop score ≤4 admitted for induction of labor at a single institution. Of these, 109 (49.5%) received the misoprostol vaginal insert and 111 (50.5%) received the dinoprostone vaginal insert. The primary outcome was the vaginal delivery rate. Secondary outcomes were time from induction to vaginal delivery, time to any delivery mode, time from induction to the onset of active labor, oxytocin use, uterine tachysystole and need for tocolysis. Results: The vaginal delivery rate was 88% in the misoprostol insert group, compared with 74% in the dinoprostone insert group ( P  < 0.007). The average time from drug administration to the beginning of labor was shorter in the misoprostol compared with the dinoprostone group (855 min vs 1740 min, P  < 0.0001). Also, the average time from administration to delivery was shorter for women receiving misoprostol compared with dinoprostone (1113 min vs 2150 min, P  < 0.0001). The use of misoprostol reduced the need for oxytocin compared with dinoprostone (30.2% vs 43.2%, P  = 0.046). Finally, compared with dinoprostone, the misoprostol insert was associated with more uterine tachysystole (38% vs 12%, P  < 0.001), but the rate of tachysystole requiring tocolysis was not significantly different between the 2 groups (51.2% vs 46.1%, P  = 0.1). Multivariate analysis showed that Bishop score and method of induction, but not maternal body mass index or gestational age at induction, were independently associated with mode of delivery. Conclusions: The cesarean section rate was significantly lower in the misoprostol insert group. The use of misoprostol was also associated with reduced time to vaginal delivery and time to onset of active labor and with decreased use of oxytocin. Tachysystole was a frequent complication during induction of labor with the misoprostol insert.